Wacana â€œAjeg Baliâ€ Pada Seni Kerajinan Sarana Upacara Di Gianyar Bali - Ni Kadek Karuni; I Wayan Suardana (Mudra Jurnal Seni Budaya, 2018)
Dalam usahaÂ  mengantisipasi tergerusnya seni budaya Bali yang adiluhung, Bali post dan Bali TV meluncurkan wacana â€œAjeg Baliâ€ yang artinya menjaga dan melestarikan identitas budaya Bali agar tidak jatuh di bawah hegemoni budaya global. Penelitian ini ingin mengungkap peranan wacana Ajeg Bali dalam meningkatkan seni kerajinan sarana upacara, dan perubahan sikap hidup masyarakat dalam melakukan upacara adat dan agama. Hal ini perlu diketahui agar konsep Ajeg Bali sesuai dengan tujuan dan sasaran yang dikehendaki.Â  Oleh karena itu, diperlukan pendekatan estetika dan sosiologi, yang dipergunakan untuk menganalisis karya seni dan perubahan sosial kehidupan masyarakat dengan adanya wacana Ajeg Bali. Metode Â penelitian yang digunakan adalah metode kualitatif dengan analisis deskriptif analitik. Hasil penelitian menunjukkan, bahwa Wacana Ajeg Bali berperan sangat besar dalam pengembangan seni kerajinan sarana upacara yang ada di Gianyar Bali. Wacana ajeg Bali ini diaktualisasikan dengan meningkatkan berbagai aktivitas upacara adat dan agama serta aktifÂ  melakukan persembahyanganÂ  ke berbagai Pura yang tersebar luas di seluruh Pulau Bali, yang disebut dengan â€œRekreasi Religiusâ€ Meningkatnya aktivitas upacara dan rekreasi religius, memerlukan berbagai sarana upacara dengan tampilan yang indah dan menarik. Para perajin melihat peluang ini sangat pontensial dan mulai mengembangkan kreativitasnya untuk menciptakan sarana upacara yang baru dengan tetap memiliki identitas Bali. Di berbagai wilayah Kabupaten Gianyar mulai banyak tersebar seni kerajinan sarana upacara seperti di kecamatan Tegallalang, Payangan, Sukawati, dan Tampaksiring. Banyaknya aktivitas upacara adat dan agama, dan tingginya keinginan masyarakat untuk memiliki sarana upacara dengan berbagai bentuk dan jenis, memberi motivasi yang tinggi pada perajin untuk menciptakan sarana upacara yang lebih unik dan menarik.In an effort to anticipate the decrease of Balinese art culture, adiluhung, Bali Post and Bali TV have published a discourse of â€œAjeg Baliâ€which means to protect and to preserve Balinese culture from falling victim to globalÂ  hegemony.Â  This research has been conducted as a means of knowing the influence discourse ofÂ  â€œAjeg Baliâ€has in increasing the art crafts of ceremonial facilities, and the changes in society's attitude in performing tradition and religious ceremony as well. These are paramount to knowing whether the concept of â€œAjeg Baliâ€is appropriate to the goal and target stated. That is why, an aesthetic and sociologicalÂ  approach is required to analyze the art works and social life changes of the society by means of discourse in â€œAjeg Baliâ€. The research method used in this study was qualitative method by analytic description.The result of this study shows that the discourse of â€œAjeg Baliâ€plays an important role in developing the art crafts of ceremonial facilities in Gianyar Bali. It is promoted through intensifying of various events such as traditional and religious ceremonies as well as ritual of prayers held in temples spread out over Bali known as â€œReligious Recreationâ€. This increase in activities of ceremony and religious recreation has led to an increasing demand for artistic and attractive facilities for various ceremonies. Craftsmen see this as a promising opportunity and begin to improve their creative process in producing new ceremonial facilities that retain Balinese identity. In Gianyar Regency, there are many craft centers producing ceremonial facilities that have begun to grow, such as those in subdistricts of Tegallallang, Sukawati, Tampaksiring, and Blahbatuh. The rise of activities of tradition and religious ceremony and the high of society willing to have ceremony facilities with various shape and type, has given high motivation to craftsmen to produce more unique and interesting ceremonial facilities.Â In an effort to anticipate the decrease of Balinese art culture, adiluhung, Bali Post and Bali TV have published a discourse of â€œAjeg Baliâ€which means to protect and to preserve Balinese culture from falling victim to globalÂ  hegemony.Â  This research has been conducted as a means of knowing the influence discourse ofÂ  â€œAjeg Baliâ€has in increasing the art crafts of ceremonial facilities, and the changes in society's attitude in performing tradition and religious ceremony as well. These are paramount to knowing whether the concept of â€œAjeg Baliâ€is appropriate to the goal and target stated. That is why, an aesthetic and sociologicalÂ  approach is required to analyze the art works and social life changes of the society by means of discourse in â€œAjeg Baliâ€. The research method used in this study was qualitative method by analytic description.The result of this study shows that the discourse of â€œAjeg Baliâ€plays an important role in developing the art crafts of ceremonial facilities in Gianyar Bali. It is promoted through intensifying of various events such as traditional and religious ceremonies as well as ritual of prayers held in temples spread out over Bali known as â€œReligious Recreationâ€. This increase in activities of ceremony and religious recreation has led to an increasing demand for artistic and attractive facilities for various ceremonies. Craftsmen see this as a promising opportunity and begin to improve their creative process in producing new ceremonial facilities that retain Balinese identity. In Gianyar Regency, there are many craft centers producing ceremonial facilities that have begun to grow, such as those in subdistricts of Tegallallang, Sukawati, Tampaksiring, and Blahbatuh. The rise of activities of tradition and religious ceremony and the high of society willing to have ceremony facilities with various shape and type, has given high motivation to craftsmen to produce more unique and interesting ceremonial facilities.